Using broadband seismic networks to optimize microgravity survey strategy in the United Kingdom. Issue 4 (27th July 2018) - Goncharenko, Yuriy; Boddice, Daniel; Rodgers, Anthony; Atkins, Philip; Metje, Nicole; Chapman, David
ABSTRACT: Microgravity measurements are a useful tool for detecting subsurface features, especially deep targets or those in conductive ground which lie outside the capabilities of other methods based on electromagnetic signal transmission. However, the method is limited by a range of noise sources including vibrational noise from the environment, one source of which being the microseism noise due to ocean waves. This noise travels through the bedrock and manifests itself in the data. It varies as a function of time and location. The effect of the wave noise on microgravity measurements in the United Kingdom was assessed for the first time using a field gravimeter (Scintrex CG5) and a link was demonstrated between the noise from microgravity measurements and those from a broadband seismometer. As a result, a new method for assessing the impact of this noise on microgravity measurements in the United Kingdom is proposed using readily available data from the continuously monitoring seismic network run by the British Geological Survey to create an accurate nowcast. Knowledge of this noise on the day of survey in conjunction with an approximate signal strength of the expected targets can be used to significantly improve survey planning in terms of the optimal observation time at which surveys for particular targets should be conducted, saving time and money on failed microgravity surveys.